A Tool Set for the Genome-Wide Analysis of Neurospora crassa by RT-PCR. Issue 10 (1st October 2015) - Hurley, Jennifer M; Dasgupta, Arko; Andrews, Peter; Crowell, Alexander M; Ringelberg, Carol; Loros, Jennifer J; Dunlap, Jay C
Abstract: Neurospora crassa is an important model organism for filamentous fungi as well as for circadian biology and photobiology. Although the community-accumulated tool set for the molecular analysis of Neurospora is extensive, two components are missing: (1) dependable reference genes whose level of expression are relatively constant across light/dark cycles and as a function of time of day and (2) a catalog of primers specifically designed for real-time PCR (RT-PCR). To address the first of these we have identified genes that are optimal for use as reference genes in RT-PCR across a wide range of expression levels; the mRNA/transcripts from these genes have potential for use as reference noncycling transcripts outside of Neurospora. In addition, we have generated a genome-wide set of RT-PCR primers, thereby streamlining the analysis of gene expression. In validation studies these primers successfully identified target mRNAs arising from 70% (34 of 49) of all tested genes and from all (28) of the moderately to highly expressed tested genes.